Perverting Play: Theorizing a Queer Game Mechanic. (May 2017) - Engel, Maureen
This article argues the possibility of building not just a queer gaming experience but rather a queer game mechanic—that is, a game whose very structure of play can be theorized as queer. It presents the prototype game Go Queer, a locative media history app, as a theoretical experiment in what it might mean to play queer. Queer theorists and historiographers have demonstrated the intimate relation between queer subjects and the city; the game literalizes this dynamic, requiring players to travel the physical spaces of the city in the hopes that they will encounter queer history—now disappeared, redeveloped, forgotten. It proposes that a productive and underrepresented setting for queer play is the space of the city itself and that the hybrid reality of locative media provides particular affordances to enable particularly queer navigations, occupations, and constructions of queer urban space.